Contesting. Issue 2 (1st June 2022) - Mitchell, Claudia
Abstract : This issue of Girlhood Studies: An Interdisciplinary Journal, while unthemed in the sense that it comes out of an Open Call, reminds us that a foundational principle of Girlhood Studies remains one of contesting and challenging inequities. Furthermore, how girls themselves might, under some circumstances, take up critical issues in their lives is evident in these contributions. Each of the contributors has placed front and centre the idea of contesting. Recently in a publications panel at a graduate student conference, participants, eager to get their work published, wanted to know more about this journal. Two of their questions stand out. "May the articles be quantitative as well as qualitative?" and "Is it enough that at least half of my participants are girls?" This collection of articles responds beautifully to these questions in offering an affirmative to the question about quantitative and qualitive data when the point is to use appropriate evidence to contest gender norms, and a negative to being about representation in terms of simply including girls.